Performance of different varieties of cashew under high density planting system - Rejani, R.; Adiga, J.D.; Yadukumar, N. (Journal of Plantation Crops, 2013)
An experiment was conducted at Directorate of Cashew Research, Puttur, Karnataka during 2006-2012 to find the suitable variety and plant density for cashew cultivation along West Coast. The experiment was laid out in a split plot design with nine cashew varieties under four plant densities and three replications. The soil moisture content was higher at the base of the plants under high density planting system (February to March) due to the shade effect by canopy. The stem girth was higher in varieties like Dhana and Bhaskara (47.7 and 45.3 cm) and lowest in VRI-3 (32.1 cm). The varieties like Ullal-3 and Bhaskara were taller than other varieties. Different plant density did not have any significant effect on plant growth except for ground coverage by canopy. The ground coverage by canopy was higher in Ullal-3 (59.7%) and Bhaskara (58.9%) and was lowest in VRI-3 (36.6%). Cumulative yield was higher in Ullal-3 (2511 kg ha–1) and Bhaskara (2493 kg ha–1). Varieties like Ullal-1, Dhana and Madakkathara-2 performed better than other varieties. Among the different plant densities, 500 plants per hectare with a mean yield of 1395 kg ha–1 was the best one. A slight increase in the levels of available N, P2O5 and K2O content in the soil with high density planting system was obtained due to the increased biomass fall out. No significant variation in nutrient content of leaf with plant density but the nutrient content varied with plant variety.